Wake steering strategies for combined power increase and fatigue damage mitigation: an LES study. Issue 2 (September 2020) - López, B; Guggeri, A; Draper, M; Campagnolo, F
Abstract: The impact of wake steering control strategy on power production and loads for a cluster of two wind turbines is analysed in this work. The power and loads data base are generated by means of high resolution simulations using an ALM-LES model along with an aeroelastic code for multibody analysis, while the optimal yaw misalignment values are obtained, for different wind directions and performance requirements, using a weighted cost function that accounts for both power production and fatigue damage on main wind turbine components. The sensitivity of the results regarding the inflow conditions, in terms of turbulence intensity, is also analysed. The overall results show that when accounting for both power production and fatigue damage, greater values of optimal yaw misalignment are obtained. This indicates that standard yaw misalignment strategies that accounts only for power production reduce at the same time the loading damage on the wind turbine, compared to greedy configuration.